The Regulatory Effect of Se-Cd Interaction on Tea Plants (Camellia sinensis (L.) O. Kuntze) Under Cadmium Stress - Yanyun Sun; Yueling Zhao; Hongyu Zhou; Faxing Li; Yuanyuan Wang; Xiao Du (Agronomy)
This study utilized annual Fuding Dabaicha cuttings as the experimental subject, employing a nutrient solution cultivation technique to establish three distinct treatments: (1) CK: reference processing; (2) Cd: 20 mg/L CdSO4 nutrient solution culture; (3) Cd + Se: 20 mg/L CdSO4 + 1.5 mg/L Na2SeO3 nutrient solution culture. We measured and analyzed the electrolyte permeability, proline content, malondialdehyde (MDA) content, antioxidant-related indicators, photosynthesis-related indicators, Cd content in various organs, and transmission electron microscopy images depicting the distribution of Cd and Se elements within different organs of tea plants under these treatments after 30 days of processing, studying the regulatory role of selenium on the resistance mechanism of tea plants (Camellia sinensis) under cadmium stress. The findings are as follows: (1) Cd stress notably elevated the electrical conductivity, MDA content, and proline content of tea plants, whereas the Cd + Se1 treatment significantly reduced the MDA and proline content under Cd stress; (2) the Cd stress treatment significantly increased the content of peroxides in the tea tree leaves and significantly decreased the activities of four antioxidant enzymes, SOD, POD, CAT, and Apx; the Cd + Se treatment significantly reduced the peroxide content in tea trees under cadmium stress and significantly increased the activities of SOD, POD, CAT, and Apx; (3) the Cd stress treatment significantly increased the values of certain chlorophyll fluorescence parameters and had no significant impact on the distribution of light energy, whereas the Cd + Se treatment significantly elevated the values of some chlorophyll fluorescence parameters and induced an uneven distribution of light energy; (4) the order of accumulation of Cd in different organs of the tea plants was as follows: root > stem > leaf, and the Cd + Se treatment significantly reduced the Cd content in various organs under Cd stress. In root cells, Cd and Se were predominantly located in the cell wall, plasma membrane, and vacuole membrane; in stem cells, they were primarily found in the cell wall and cytoplasm adjacent to the cell wall; in leaf cells, they were mainly distributed in the plasma membrane, cytoplasm, and vacuole. In conclusion, Cd treatment induced stress in tea plants, which resulted in a certain stimulatory effect on photosynthesis, but caused some damage to the photosynthetic apparatus in chloroplasts. The results of the Cd + Se treatment suggest that the interaction between Se and Cd can mitigate the toxicity experienced by tea plants under Cd stress.